Influence of pressure and time on extraction process using supercritical CO2 - Mićić V.; Lepojević Ž.; Mandić B.; Jotanović M.; Tadić G.; Tolić A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The supercritical fluid extraction (SFE) by carbon dioxide (CO2) of Salvia officinalis L. was investigated. SFE by CO2 was performed at different pressure (80, 100, 150, 200 and 300 bar) and constant temperature of 40ºC (all other extraction conditions, such are flow rate, particle diameter of Salvia officinalis, extraction time were kept constant. The GC-MS method was used for determination of qualitative and quantitative composition of obtained extracts and essential oils.